Understanding the Impact of Armed Conflict on Women's Lives in Kashmir: A Sociological Analysis - Amjad, Uzair (Sociological Research And Innovation, 2023)
This article provides a comprehensive analysis of the impact of armed conflict on the lives of women in Kashmir, using a sociological perspective. It examines how women are affected by the conflict, exploring their experiences of violence, displacement, and loss. The study draws on existing literature, personal narratives, and interviews with women in the region to share insights into the gendered dimensions of the conflict. The article argues that an understanding of women's experiences is crucial for developing effective peacebuilding strategies that address the needs of all members of society. The Kashmir conflict, a protracted and enduring conflict in South Asia, has led to significant violence, displacement, and loss of life, particularly affecting women in the region. The conflict has taken various forms, including armed insurgency, terrorism, state violence and house arrests. Women in Kashmir face unique challenges, including restrictions on mobility, limited access to healthcare and education, and gender-based violence. Despite numerous attempts at peace talks, the conflict remains unresolved, creating a climate of fear and mistrust. This article contributes to the existing literature by providing a comprehensive analysis of the impact of armed conflict on women in Kashmir. It highlights the need for adopting gender-sensitive peacebuilding strategies that prioritize the needs and perspectives of women. The findings emphasize the importance of integrating women's voices and perspectives in all aspects of the peacebuilding process to build sustainable peace in Kashmir.